PENGARUH KOMPETENSI TIK GURU, KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA ( Studi di SMP Negeri Sub Rayon 05 Kota Semarang ) - 11.52.02.0152, Sri Turahwati (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study aimed to analyze the influence teachers ICT Competence, principal leadership, organizational culture and job satisfaction on teacher performance in public junior high school Sub Rayon 05 Semarang. The population numbered 175 people, consisting of public junior high school teachers in Sub Rayon 05 Semarang. There are 175 questionnaires were distributed but only 161 people who return the questionnaires. Methods of data collection using primary data is data obtained from the answers (responses) of respondents to a series of questions that have been posed in the questionnaire related to teachers ICT Competence, principal leadership, organizational culture, job satisfaction and teacher performance complete with identities such responders name, age, class etc.. The collected data were analyzed using SPSS 19 to test the respondents descriptions, descriptions of variables, validity, reliability, classical assumptions, models and hypotheses. Results of data analysis showed that teachers ICT Competence has no effect on job satisfaction but a positive significant effect on teacher performance, principal leadership significant positive effect on job satisfaction but had no effect on teacher performance, organizational culture significant positive effect on job satisfaction and teacher performance, job satisfaction significant positive effect on teacher performance and the mediating effect of principal leadership on teacher performance but does not mediate the influence of teachers ICT competence and organizational culture on teacher performance. Keywords: Teachers ICT Competence, Principal Leadership, Organizational Culture, Job Satisfaction and Teacher Performance